Penfluridol suppresses pancreatic tumor growth by autophagy-mediated apoptosis - Ranjan, Alok; Srivastava, Sanjay K. (Scientific reports, 2016)
Pancreatic tumors exhibit enhanced autophagy as compared to any other cancer, making it resistant to chemotherapy. We evaluated the effect of penfluridol against pancreatic cancer. Penfluridol treatment induced apoptosis and inhibited the growth of Panc-1, BxPC-3 and AsPC-1, pancreatic cancer cells with IC 50 ranging between 6–7 μM after 24 h of treatment. Significant autophagy was induced by penfluridol treatment in pancreatic cancer cells. Punctate LC3B and autophagosomes staining confirmed autophagy. Inhibiting autophagy by chloroquine, bafilomycin, 3-methyladenine or LC3BsiRNA, significantly blocked penfluridol-induced apoptosis, suggesting that autophagy lead to apoptosis in our model. Penfluridol treatment suppressed the growth of BxPC-3 tumor xenografts by 48% as compared to 17% when treated in combination with chloroquine. Similarly, penfluridol suppressed the growth of AsPC-1 tumors by 40% versus 16% when given in combination with chloroquine. TUNEL staining and caspase-3 cleavage revealed less apoptosis in the tumors from mice treated with penfluridol and chloroquine as compared to penfluridol alone. Penfluridol treatment also suppressed the growth of orthotopically implanted Panc-1 tumors by 80% by inducing autophagy-mediated apoptosis in the tumors. These studies established that penfluridol inhibits pancreatic tumor growth by autophagy-mediated apoptosis. Since penfluridol is already in clinic, positive findings from our study will accelerate its clinical development.